Biofloc Technology in Fish Aquaculture: A Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Kyung Mi Lee; Jun-Hwan Kim (MDPI AG, 2023)
The application of biofloc to fish species has several advantages, including the enhancement of production by increasing growth performance and survival rate and the improvement of fish aquaculture physiological activity. There has been a recent increase in biofloc addition to fish culture, and this review examines changes this causes to the survival and growth rate of fish and its economic feasibility. Physiological activity and disease resistance of biofloc-fed fish is being extensively studied. The hematological parameters and antioxidant and immune responses of fish fed biofloc were reviewed in this study, as well as their disease resistance by testing them for major specific diseases. Standards for effectively applying biofloc to fish aquaculture are also suggested.